2018
DOI: 10.7759/cureus.2635
|View full text |Cite
|
Sign up to set email alerts
|

Erythema Ab Igne from Heating Pad Use: A Report of Three Clinical Cases and a Differential Diagnosis

Abstract: Erythema ab igne is an asymptomatic cutaneous disorder characterized by erythematous reticulated hyperpigmentation resulting from chronic exposure to infrared radiation in the form of heat. We report three cases of erythema ab igne from chronic heating pad use over a duration of six months to three years. The lesions were asymptomatic in all three patients and were incidental skin findings in two patients, unrelated to their chief complaints. This illustrates the importance of recognizing the morphology and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Aria et al [ 11 ] describe other dermatologic conditions occurring in various age groups that also present with a similar reticulated pattern to erythema ab igne. Examples include cutis marmorata and livedo racemosa.…”
Section: Discussionmentioning
confidence: 99%
“…Aria et al [ 11 ] describe other dermatologic conditions occurring in various age groups that also present with a similar reticulated pattern to erythema ab igne. Examples include cutis marmorata and livedo racemosa.…”
Section: Discussionmentioning
confidence: 99%
“…With this extended and repeated heat exposure, damage to the superficial blood vessels leads to hemosiderin deposition. Over time, it leads to the development of hyperpigmentation, hyperkeratosis, as well as hyper-elastosis of the exposed skin [8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic changes also depend on the type of heat source. 10,13,22,23 In one study, it has been shown that moderate heat acts synergistically with ultraviolet radiation to denature DNA in in vitro squamous cells. 22 Bullous EAI is a rare variant of this dermatosis.…”
Section: Discussionmentioning
confidence: 99%